Social media homicide confessions : stories of killers and their victims - Yardley, Elizabeth (Policy Press, 2017)
"As our interactions with others become ever more mediated by various forms of electronic communication, the relationship between crime and technology is becoming an increasingly important topic for both theoretical and practical studies of criminology. This book analyses digital communications as they play a part in contemporary homicide, drawing on a range of cases from the United Kingdom and elsewhere in the world -- cases where killers confessed on social media, for example, or where their actions were traced using their digital communications. Offering a groundbreaking conceptual framework for people studying this issue, the book will be of great value to criminologists, students, and police officers."--